Molecular basis of rutin inhibition of protein disulfide isomerase (PDI) by combined in silico and experimental methods. Issue 33 (21st May 2018) - Wang, Xu; Xue, Guangpu; Song, Meiru; Xu, Peng; Chen, Dan; Yuan, Cai; Lin, Lin; Flaumenhaft, Robert; Li, Jinyu; Huang, Mingdong
Abstract : Rutin binds and inhibits PDI at b′x domain, H354 is one of the main binding sites. Abstract : Protein disulfide isomerase (PDI) is a founding member of the thiol isomerase family, and is recently found to play critical roles in thrombus formation. The development of effective PDI inhibitors is of great significance, and attracts strong interest. We previously showed that rutin bound directly to PDI and inhibited PDI activities, leading to the suppression of platelet aggregation and fibrin generation in a mouse model. A close analog of rutin, isoquercetin, is currently in advanced phase clinical trials. However, the molecular interaction between rutin and PDI is unknown and is difficult to study by X-ray crystallography due to the weak interaction. Here, we generated a molecular model of PDI:rutin complex by molecular docking and thorough molecular dynamics (MD) simulations. We then validated the complex model through a number of different experimental methods. We mutated the key residues predicted by the model and analyzed the mutants by an optimized isothermal titration calorimetry (ITC) method and a functional assay (insulin reduction assay). The results consistently showed that the PDI residues H354, L355 and E359 are important in the binding of rutin. These residues are next to the canonical major substrate binding site of the b′ domain, and were not conserved across the members of thiol isomerases, explaining the specificity of rutin for PDI among vascular thiol isomerases. Furthermore, the inhibitory activities of three rutin analogues were evaluated using an insulin reduction assay. The results supported that the second sugar ring at the side chain of rutin was not necessary for the binding to PDI. Together, this work provides the structural basis for the inhibitory mechanism of rutin to PDI, and offers a promising strategy for the design of new generation inhibitors with higher binding affinity to PDI for therapeutic applications.